PENERAPAN STANDARD AKUNTANSI INTERNASIONAL OLEH PERUSAHAAN PUBLIK DI INDONESIA - Nang D. Gunawan; Heru Satyanugraha (Media Riset Akuntansi, Auditing & Informasi, 2005)
Adopting international accounting standard shall be beneficial to fins listed in stock exchange. This research investigates the extent to which the disclosure require-ment of Intemational Accounting StandardsliAS-1) for presentation of financial state-ments are complied by the listed companies in Jakarta Stock Exchange. The financial reports of 280 companies listed in Jakarta Stock Exchange were examined. The study concludes that in general listed companies in Jakarta do not comply fully with lAS-1 requirements. In items of "components of financial statements", "disclosure of income statement", 'timeliness", "comparability", "stock information" they do comply with the international standard. For the other items, " compliance", "going concern", °divi-dend", "description of reserves", "reclassification", they tend not to comply with the requirements. The study found also there are differences of size of the companies toward "timeliness' and "disclosure", differences of types of auditor on compliance to "disclosure", and pmfitability of the companies on "going concern".Key words : compliance, financial report, accounting standard, intemational, jakarta stock exchange,